Physical violence against women by their intimate partner during pregnancy and its relationship with breastfeeding - Aristizábal,Liliana Yanet Gómez (2022)
Abstract Objectives: to estimate the association between physical violence against women by their intimate partner during pregnancy and breastfeeding. Methods: the data source is the 2010 National Demographic and Health Survey (DHS) conducted in Colombia, and 11,416 mother-child dyads were analysed. The relationship between physical violence against women by their partner during pregnancy and breastfeeding indicators was carried out using the weighted propensity score from the Inverse Probability of Treatment Weighting (IPTW). Variables for adjustment were selected through the Directed Acyclic Diagram (DAG) and performed a sensitivity analysis to identify the strength of hidden bias. Results: according to the data, 6.4% (730) of the women suffered physical violence by their partner during their pregnancy. The median time of exclusive breastfeeding was 1.0 month. No statistically significant relationship was observed with any of the breastfeeding indicators analysed: exclusive breastfeeding (OR=1.17; CI95%=0.82-1.67); breastfeeding at any time (OR=1.61; CI95%=0.58-2.60); and initiation of breastfeeding (OR=1.07; CI95%=0.74-1.2) Conclusion: although the association between violence against women committed during pregnancy and breastfeeding indicators was not found, the suboptimal breastfeeding practices and high prevalence of violence against women by the partner are two major public health issues in Colombia. Prenatal care professionals can change this scenario by identifying women exposed to intimate partner violence and offering tailored support for breastfeeding practices.